ANALISIS DAMPAK INTEGRASI ESG PADA PROFIL RISIKO-RETURN PORTOFOLIO INVESTASI - Ferix Aziz Susandi; Danu Purwito; Bagus Eka Prasetya; Sayekti Suindyah Dwiningwarni (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This research aims to analyze the impact of Environmental, Social, and Governance (ESG) integration on the risk-return profile of the investment portfolio of PT Unilever Indonesia Tbk. The research employs a quantitative method with a case study approach, utilizing historical data from the period 2017-2021. The data is analyzed to identify the relationship between ESG scores and portfolio returns, as well as portfolio risk. Regression analysis and t-test are employed to test the research hypotheses. The findings reveal a positive and significant relationship between ESG integration and the investment portfolio's return of PT Unilever Indonesia Tbk. The regression coefficient of 0.154 indicates that each one-point increase in the ESG score will result in an average increase of 0.154% in the investment portfolio return.